2014
DOI: 10.1155/2014/104823
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Boron Compounds for the Modification of Suberoyl Anilide Hydroxamic Acid as Inhibitor of Histone Deacetylase Class II Homo sapiens

Abstract: Histone deacetylase (HDAC) has a critical function in regulating gene expression. The inhibition of HDAC has developed as an interesting anticancer research area that targets biological processes such as cell cycle, apoptosis, and cell differentiation. In this study, an HDAC inhibitor that is available commercially, suberoyl anilide hydroxamic acid (SAHA), has been modified to improve its efficacy and reduce the side effects of the compound. Hydrophobic cap and zinc-binding group of these compounds were substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 65 publications
0
14
0
1
Order By: Relevance
“…Recent studies have been trying to find strategies to identify highly toxic BCCs by employing analytical chemistry, the quantitative structure-activity relationship (Endo, 2003;Dembitsky, 2004;Zhang, 2014;Hansen, 2015;Pellizzaro, 2015), and/or computational predictive assays (Ciani, 2012;Kehlert, 2013;Bakri, 2014). Most of these studies have suggested that specific moieties in aryl or alkyl boronic acids are likely to be responsible for inducing cytotoxicity or mutagenicity (Pellizzaro, 2015).…”
Section: The Origins Of Avoidance Of Bccs In Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have been trying to find strategies to identify highly toxic BCCs by employing analytical chemistry, the quantitative structure-activity relationship (Endo, 2003;Dembitsky, 2004;Zhang, 2014;Hansen, 2015;Pellizzaro, 2015), and/or computational predictive assays (Ciani, 2012;Kehlert, 2013;Bakri, 2014). Most of these studies have suggested that specific moieties in aryl or alkyl boronic acids are likely to be responsible for inducing cytotoxicity or mutagenicity (Pellizzaro, 2015).…”
Section: The Origins Of Avoidance Of Bccs In Medicinementioning
confidence: 99%
“…These models are only able to predict whether compounds are toxic or non-toxic within a single toxicity class. Also, in silico analysis of BCCs has yielded limited results when using Lipinski's rule or predictors based on pharmacokinetics and pharmacodynamics (Bakri, 2014). With innovative strategies, some researchers are trying to build a multiclass model to predict several categories of toxicity (e.g., acute toxicity, mutagenicity, tumorigenicity, skin and eye irritation, reproductive effects and multiple dose effects) by using databases instead of only one or two toxicity endpoints (Chen, 2013;Raies, 2016).…”
Section: The Origins Of Avoidance Of Bccs In Medicinementioning
confidence: 99%
“…Unsurprisingly, HDACi research over the past decade has focused on the design of HDAC3 and HDAC8 inhibitors due to their significant structural differences. [31,[52][53][54][55] To date, integration of boron moieties into HDAC inhibitors such as 1 has only had limited success, with their in vitro potency being surpassed by more traditional organic fragments. Previous work in this field has focussed on the re-design the skeletal structure of 1 by altering either 1) its linker or 2) Zn 2 + -binding domain to improve the drug's metal-complexation capability.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, such studies have solely focused on the use of boronic acids to coordinate to the Zn 2 + ion in Class I, II and IV HDACs but with only limited success. [29][30][31] To date, hydroxamic acid-based drugs such as 1 are still amongst the most potent inhibitors of Class I HDACs. [20,26,32,33] To the best of our knowledge, modification of the phenyl capping group in 1 with boron moieties has not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…Penggunaan piranti-piranti lunak daring tersebut banyak diarahkan untuk pengembangan obat dengue, avian influenza, dan kanker serviks (Wei et al, 2006;Lim et al, 2013;Bakri et al, 2014). Secara lebih detail, beberapa aspek penting dalam desain obat in silico meliputi: (1) metode komputasional pada polifarmakologi, (2) prediksi parameter farmakokinetik, (3) teknologi CADD pada desain obat secara in silico, (4) prediksi potensial aksi, (5) aplikasi OMICs di biologi sel punca, (6) komputasi basis data lncRNAs berbasis internet dibahas di dalam kajian ilmiah ini.…”
Section: Bioinformatika Dalam Bidang Kesehatan Dan Desain Obat Secaraunclassified